Impact of chronic kidney disease in 29 893 patients undergoing transcatheter or surgical aortic valve replacement from the German Aortic Valve Registry. (17th January 2021) - Mas-Peiro, Silvia; Faerber, Gloria; Bon, Dimitra; Herrmann, Eva; Bauer, Timm; Bleiziffer, Sabine; Bekeredjian, Raffi; Böning, Andreas; Frerker, Christian; Beckmann, Andreas; Möllmann, Helge; Vasa-Nicotera, Mariuca; et al.
Abstract: OBJECTIVES: Chronic kidney disease (CKD) is a key risk factor in patients undergoing transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (SAVR). We analysed the impact of estimated glomerular filtration rate (eGFR) and CKD stages on their mid-term survival. METHODS: Data from 29 893 patients enrolled in the German Aortic Valve registry from January 2011 to December 2015 receiving TAVI ( n  = 12 834) or SAVR ( n  = 17 059) at 88 sites were included. The impact of renal impairment, as measured by eGFR and CKD stages, was investigated. The primary end-point was 1-year cumulative all-cause mortality. RESULTS: Higher CKD stages were significantly associated to lower in-hospital, 30-day- and 1-year survival rates. Both TAVI- and SAVR-treated patients in CKD 3a, 3b, 4 and 5 stages showed significant and gradually increasing HR values for 1-year all-cause mortality. The same trend persisted in multivariable analysis, although HR values for CKD 3a and 5 did not reach significance in TAVI patients, whereas CKD 4 + 5 did not reach statistical significance in SAVR. Likewise, eGFR as a continuous variable was a significant predictor for 1-year mortality, with the best cut-off points being 47.4 ml/min/1.73 m 2 for TAVI and 59.8 ml/min/1.73 m 2 for SAVR. Significant 8.6% and 9.0% increases in 1-year mortality were observed for every 5-ml reduction in eGFR for TAVI and SAVR, respectively. CONCLUSIONS: CKD ≥3b and CKD ≥3a are the independent major risk factors for mortality in patients undergoing TAVI and SAVR, respectively. In the overall population of patients with severe aortic stenosis, an appropriate stratification based on CKD substage may contribute to a better selection of patients suitable for such therapies.